2010
DOI: 10.1159/000288758
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Screening in Asia: Recognizing the Role of the Patient-Family Unit

Abstract: Background/Aims: Cognitive screening programmes may improve awareness and help at-risk subjects receive earlier medical attention. Cognitive profiles of subjects who attend cognitive screening by personal choice (self-referred) compared to those where the referral was initiated by family members (family-referred) were compared. Methods: A cross-sectional survey of community subjects attending a cognitive screening initiative. Performance on the MMSE, Frontal Assessment Battery (FAB), Elderly Cognitive Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…They might be unaware of their cognitive changes (Ausen et al , ); or might be culturally socialized to assess their own cognitive abilities differently (Wong et al , ). In such situations, these older adults would be most prone to receive medical attention for their declined cognition much later (Roe et al , ; Ng et al , ). Collateral information and qualitative analysis of informants' contributions can inform diagnostic decisions and also guide research efforts (Arlt et al , ).…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…They might be unaware of their cognitive changes (Ausen et al , ); or might be culturally socialized to assess their own cognitive abilities differently (Wong et al , ). In such situations, these older adults would be most prone to receive medical attention for their declined cognition much later (Roe et al , ; Ng et al , ). Collateral information and qualitative analysis of informants' contributions can inform diagnostic decisions and also guide research efforts (Arlt et al , ).…”
Section: Designmentioning
confidence: 99%
“…Thus, there is an urgent need to increase understanding of the presentation of MCI in this population. In fact, studies in both Asia and the United States have shown that low education is not only a risk factor for dementia, but it also decreases the chance for detecting MCI or the earlier stages of dementia (Roe et al , ; Ng et al , ). As an added challenge, the need to include social and cultural factors for interpreting test scores obtained by older adults with low education further highlight the need for more research on this population (Gomez et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation